2020
DOI: 10.1093/mnras/stz3621
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of unresolved and unclassified sources detected in radio continuum surveys of the Galactic plane

Abstract: The continuum emission from 1 to 2 GHz of The H i/OH/Recombination line survey of the inner Milky Way (THOR) at ≲18 arcsec resolution covers ∼132 deg2 of the Galactic plane and detects 10 387 sources. Similarly, the first data release of the Global View of Star Formation in the Milky Way (GLOSTAR) survey covers ∼16 deg2 of the Galactic plane from 4 to 8 GHz at 18 arcsec resolution and detects 1575 sources. However, a large fraction of the unresolved discrete sources detected in these radio continuum surveys of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Preliminary results of a study focused on the unresolved unidentified sources with negative spectral index (∼340 sources of the present catalog), such as was performed by Chakraborty et al (2020), indicated that differential source counts in the distribution trend of extragalactic sources result from other surveys or catalogs. However, we recall that the observed fields are in the surroundings of the Galactic plane, dense in Galactic sources, both of thermal and nonthermal nature.…”
Section: Search For Counterpartsmentioning
confidence: 66%
“…Preliminary results of a study focused on the unresolved unidentified sources with negative spectral index (∼340 sources of the present catalog), such as was performed by Chakraborty et al (2020), indicated that differential source counts in the distribution trend of extragalactic sources result from other surveys or catalogs. However, we recall that the observed fields are in the surroundings of the Galactic plane, dense in Galactic sources, both of thermal and nonthermal nature.…”
Section: Search For Counterpartsmentioning
confidence: 66%
“…In addition to many sources that are located in the Milky Way, there is also a large number of extragalactic sources in the survey. While these sources were not the main focus of the survey, they are an interesting by-product (e.g., Chakraborty et al 2020).…”
Section: Continuummentioning
confidence: 99%
“…For indices between −0.1 and 2, the emission corresponds to thermal emission that is associated with Hii regions or planetary nebulae (PNe). If it is steeply negative, that is ≤0.5, we consider it to be non-thermal, which means the emission is synchrotron in nature and could come from supernova remnants (SNR) or extra-galactic sources such as active galactic nuclei (AGN) (Condon 1984;Rodríguez et al 2012;Dzib et al 2013;Chakraborty et al 2020). We record the values of the spectral indices in Table A.1.…”
Section: Spectral Indexmentioning
confidence: 99%